PLK1 in cancer therapy: a comprehensive review of immunomodulatory mechanisms and therapeutic opportunities - Wang, Weihao; Zhao, Rui; Wang, Yahui; Pan, Liying; Luan, Fang; Fu, Guobin (Frontiers in Immunology, 2025)
PLK1 plays a crucial role in cell cycle regulation and cancer development, and its dysregulation has been implicated in the prognosis of a variety of malignancies. The potential of PLK1 inhibitors as cancer therapeutics has been extensively investigated. However, the underlying biology and mechanisms of PLK1 remain incompletely understood. In recent years, numerous studies have demonstrated that PLK1 overexpression is associated with resistance to certain chemotherapeutic agents, while its inhibition can enhance the efficacy of chemotherapy. In addition, PLK1 inhibitors have been shown to selectively target cancer cells as radiation sensitizers and exert synergistic effects in combination immunotherapy. The underlying mechanisms may involve the regulation of multiple immune cells and inflammatory factors, as well as alterations in the tumor microenvironment, ultimately influencing tumor genesis, migration, and invasion. Moreover, PLK1 can regulate the expression of immune checkpoint-related proteins, thereby playing a synergistic role in cancer therapy. Furthermore, PLK1 represents a promising target antigen for cancer immunotherapy, with potential applications in optimizing cancer vaccines. Therefore, this review focuses on the applications and underlying mechanisms of PLK1 in tumor immunotherapy, aiming to provide new insights for improving patient outcomes and prognosis.